Differences in Macronutrient and Micronutrient Intake of Stunted Toddlers in Rural and Urban Areas of Bengkulu Province - Suryani, Desri; Kusdalinah, Kusdalinah; Pratiwi, Bintang Agustina; Yandrizal, Yandrizal (Universitas Airlangga, 2024)
Stunting prevalence in Kepahiang District is the highest compared to other districts. In Bengkulu, the incidence rate is lower than in other districts. Dietary intake is a direct factor causing stunting. This study examines the differences in macronutrient and micronutrient intake in stunted toddlers in rural and urban areas of Bengkulu Province. The study, with a cross-sectional design, was conducted from August to September 2020. A sample of 134 toddlers aged 12-24 months was selected using accidental sampling. Dietary intake data were collected using the Semi-Quantitative Food Frequency Questionnaire (SFFQ), and other data were collected through questionnaires. The collected data were analyzed using univariate and bivariate analyses with T-tests and Mann-Whitney tests. Macronutrient intake in stunted toddlers in rural areas was lower than in urban areas. Micronutrient intake in rural areas was also lower than in urban areas, except for vitamin A. Statistically, there were no differences in macronutrient (carbohydrates, proteins, fats) and micronutrient (vitamin A, calcium, phosphorus, iron, zinc) intake between rural and urban toddler in relation to stunting (p > 0.05). Based on the data obtained, the overall nutrient intake provided to the toddlers has not met the toddlers' nutritional needs. Regular counselling sessions from house to house for mothers with stunted toddlers are necessary. This would enable mothers to understand better their toddlers' dietary needs and how to monitor their growth.